Responsabilidade civil do empregador pelo exercício de atividade de risco: da incidência às excludentes - Supioni, Adriana Jardim Alexandre (2015)
The research formulated on this study intends establish the scientific study application of the single paragraph of Article 927 of the Civil Code in labor relations since the incidence to removal of duty indemnify that can alleged as means of defense to employer. The article includes a general clause of objective liability that imposes the duty to repair, without fault, the damages caused by activities envolving risks for rights of others. In view of the forecast of article 7, XXVIII, of the Constitution which establishes the necessity the presence of employer s fraud or fault that to arise the duty to indemnify the damages suffered for your employees, we need establish the integration of the civilian an constitutional articles for to verify the possibility application in labor relations. We elected the French Revolution as a historical milestone for the development of the risk theory and, from there, it was possible to demarcate the social changes that have transformed the former of individualist thinking for the development of social as a new paradigm of legal relations with the overcoming of 19th century codes and the development of post positivistic hermeneutics. In this perspective, we search for an integrated interpretation of the constitutional and civil articles using the historical cultural hermeneutics and the legislative technique, which includes the general norms and undefined legal concepts. Overcome the constitutional issue, we analyze the assumptions of objective liability in labor relations, establishing the criteria for identifying activities that involve risk, causation, damages and the criteria for their repair. The exclusive are analyzed in the fourth chapter, specifically in relation to those who break the causal link and therefore are able to broke the duty to indemnify in the event of impact of activities involving risks. In the final chapter, we established some considerations that aim to balance the system, in view of the constitutional principles of human dignity, social value of work and free enterprise, proposing that society achieve your objective: the mutual good